THE DESIGN OF ACCOUNTING INFORMATION SYSTEM OF RECEIPTS ANF CASH DISBURSEMENT USING PAYMENT GATEWAY METHOD AT PT MAXCHAT INOVASI INDONESIA - Yulfi Haniyah Farasary; Kartika Dewi Sri Susilowati; Kurnia Ekasari (Yayasan Education and Social Center, 2023)
This study aims to design an accounting information system for cash receipts and disbursements using the existing payment gateway method at PT Maxchat Inovasi Indonesia. Data collection methods used are field research methods, interviews and literature study. While the development of the software system that the author uses uses an agile model. The information technology used in this research is Bizagi, MySQL application, and Midtrans Payment Gateway. This research was conducted at PT Maxchat Inovasi Indonesia. Based on the discussion in this research, the suggestion for the object, namely PT Maxchat Inovasi Indonesia, is to evaluate ongoing business processes including responsibilities according to the job description. Suggestions for future researchers are expected to be able to innovate and explore optimally